PENGARUH DUKUNGAN ORGANISASIONAL PERSEPSIAN ATAS KREATIVITAS, SELF-EXPANSIVENESS, DAN KEINGINAN TUMBUH PADA KINERJA KREATIF LAPORAN DIRI - , DESY MAYASARI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This article develops a framework to understand creativity in interactionist perspective. This study examines individual differences (self-expansiveness and the growth need strength) interacted with situational variables (perceived organizational support for creativity) in influencing the self-reported creative performance. Two hundred-and sixty-one (261) respondents participated in this study. This study confirmed that individuals with a growth need strength, personal self-expansiveness level and perceived organizational support for creativity, and interaction between perceived organizational support for creativity and the growth need strength have a positive effect on self-reported creative performances. Interesting results came when individuals with high personal self-expansiveness level as a unique person, cannot produce self-reported creative performance if perceived organizational support for creativity feel overwhelmed due to mandatory generate self-reported creative performances.